Vibrational Spectroscopic Studies into Impurities in Ionic Liquids - Maxwell-Hogg, Steven (2019)
Additional components present within an ionic liquid (IL) system have readily shown to alter the physiochemical properties and spectroscopic characteristics of the parent IL. Vibrational spectroscopy has been proven to be a powerful tool in probing these systems and identifying spectral changes as a result of the changing environment.